AKIBAT HUKUM DAN TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH (PPAT) ATAS COVERNOTE MENGENAI PEMBEBANAN HAK TANGGUNGAN - , ARI TRI WIBOWO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to determine the legal consequences and liability upon the issuance of covernote concerning mortgage either requested by the Bank as a loan creditor or by the debtor in the credits. This research uses an empirical normative research method. Normative empirical research method consisted of secondary data and primary data, secondary data compiles the official documents, books, research results that are closely related to the problem of this research, field research is research conducted by collecting data directly stepping off to research sites. This research was used to obtain direct primary data in the form of information obtained directly by interviewing the informants that carry out the activities of the problems in this study at research sites. Interviews were conducted because in this way will be acquired in-depth description of the informant. Due to the researcher's consideration armed with the knowledge of the population to choose the sample members, a purposive sampling and judgmental sampling are used to the subjects of this research. Results and discussion suggests that LDO's liability upon Covernote concerning mortgage, the concerned parties may sue a default or unlawful act, it depends on the content of Covernote,